Achievable region of reliabilities in multiple hypotheses two-stage testing for the pair of families of distributions - Hormozi-Nejad, Farshin (International Journal of Applied Mathematical Research, 2014)
The achievable region of reliabilities in the model with several possible hypothetical probability distributions partitioned into the pair of families is considered. The achievable region for many hypotheses testing was examined by Tuncel. Decisions concerning realized probability distribution of the object must be made on the base of the samples which are received in each stage of the two-stage test. It is proved that the defined region for the vectors of reliabilities in the two-stage test characterizes the set of all achievable vectors and advantages of the two-stage testing are revealed. Keywords: LAO test, method of types, multiple hypotheses testing, reliability, two-stage test.